CROWN Endorses a Core Outcome Set for Studies on Preterm Birth Prevention. Issue 4 (July 2016) - N/A,
Abstract : A core outcome set, an agreed standard set of outcomes that should be measured and reported as a minimum in all effectiveness trials for preterm birth prevention, has been developed using robust consensus methods with input from CROWN journals (www.crown-initiative.org) acting as a stakeholder group. MCN is one of the CROWN journals that participated in this important project.